Computational fluid dynamics and artificial neural networks for modelling lined irrigation canals with low‐density polyethylene and cement concrete liners - Eltarabily, Mohamed Galal; Elshaarawy, Mohamed Kamel; Elkiki, Mohamed; Selim, Tarek (Irrigation and drainage, 2024)
This study numerically investigated the lining effect on the discharges and seepage losses of five reaches which belong to the El‐Sont Canal, Asyut, Egypt, using FLOW‐3D and Slide2 models, respectively. Two lining materials were considered, cement concrete (CC) and CC with low‐density polyethylene (LDPE) film. A cost analysis was performed to explore the feasibility of the proposed lining materials. Moreover, a parametric study was conducted by the Slide2 model to investigate the effect of canal geometry and liner properties on seepage losses. An artificial neural network (ANN) model was developed based on the Slide2 model scenarios to estimate the seepage losses from lined irrigation canals. The results showed that reach the discharge calculated from the FLOW‐3D model increased by 92%–97% and 149%–156%, while the calculated seepage losses from the Slide2 model decreased by 81%–87% and approximately 97% under CC and CC with LDPE film liners, respectively. Cost analysis revealed that the overall cost of CC with LDPE film was higher by 14% than CC. Relying on the importance of saving irrigation water and conveying water to the last reaches, CC with LDPE film is recommended for lining irrigation canals. A parametric study showed that the seepage losses were reduced by more than 96% when the ratio between liner and soil hydraulic conductivities was less than 0.01. A thick liner could maximally decrease the seepage losses by 68%, regardless of the canal geometry. As the developed ANN model showed a close agreement with the Slide2 results with coefficient of determination (R2) and mean squared error values of 0.99 and 0.05, respectively, the ANN model is recommended as a robust and rapid tool for estimating seepage losses from lined irrigation canals. Résumé Cette étude a étudié numériquement l'effet du revêtement sur les rejets et les pertes par infiltration de cinq tronçons appartenant au Canal d'El‐sont, à Asyut, en Egypte, à l'aide de modèles FLOW‐3D et Slide2, respectivement. Deux matériaux de revêtement ont été considérés, le béton ciment (CC) et le CC avec film de polyéthylène basse densité (LDPE). Une analyse des coûts a été effectuée pour étudier la faisabilité des matériaux de revêtement proposés. De plus, une étude paramétrique a été réalisée par le modèle Slide2 pour étudier l'effet de la géométrie du canal et des propriétés du revêtement sur les pertes par infiltration. Un modèle ANN a été élaboré à partir des scénarios du modèle Slide2 pour estimer les pertes par infiltration des canaux d'irrigation revêtus. Les résultats ont montré que les rejets de tronçon calculés à partir du modèle FLOW‐3D ont augmenté de 92 à 97% et de 149 à 156%, tandis que les pertes par infiltration calculées du modèle Slide2 ont diminué de 81 à 87% et d'environ 97% sous le CC et le CC avec des revêtements en film de LDPE, respectivement. L'analyse des coûts a révélé que le coût global du CC avec film LDPE était plus élevé de 14% que le CC. Compte tenu de l'importance d'économiser l'eau d'irrigation et de transporter l'eau jusqu'aux dernières tronçons, le CC avec film LDPE est recommandé pour le revêtement des canaux d'irrigation. Une étude paramétrique a montré que les pertes par infiltration étaient réduites de plus de 96% lorsque le rapport entre la conductivité hydraulique du revêtement et du sol était inférieur à 0,01. Un revêtement épais pourrait réduire au maximum les pertes par infiltration de 68%, quelle que soit la géométrie du canal. Comme le modèle ANN développé a montré une étroite concordance avec les résultats de la Slide2 avec des valeurs R2 et MSE de 0,99 et 0,05, respectivement, ANN est recommandé en tant qu'outil robuste et rapide pour estimer les pertes par infiltration des canaux d'irrigation revêtues.